DEVELOPMENT OF DIGITAL MARKETING IN UZBEKISTAN - Dilrabo Usmanova (Journal Park Publishing, 2023)
In this article discusses about development of digital marketing in Uzbekistan.
Keywords: digital marketing, marketing digital, economics.